Web based secondary mathematics learning (SML) system: Analysis and a proposal of the development - Othman, Mohd Khalit; Ng, Xue Hong (2007)
The advent of E-learning gives a significant impact in education environment due to there are many advance features to make the system more effective to its target-users, for example multimedia contents and real time quizzes or tests. The purpose of this study/paper is to present a proposal of a Mathematics E-learning system called Secondary Mathematics Learning (SML) system. This Secondary Mathematics Learning (SML) system consist the interactive Mathematics education for all the secondary school students. There are two modules in this system, which are the teaching module and learning module. This study/paper also presented problem statements, project objectives, project scopes, and project research which include the survey analysis data in secondary school. In order to get the information for the survey analysis, the 250 sets of questionnaires have been distributed to the selected randomly students and 50 sets of questionnaires to the mathematic teachers, as respondent to get their opinion and perception. This study/paper also explains the system design and development which include the functional flow diagram, examples of module’s print screen and selection tool list. Finally, this study/paper also includes the development methodology of the project and some suggestion that can further advance the system.